The Filtered Face of Beauty: The Mediating Role of Self-Esteem in the Association Between TikTok Algorithmic Filters and Skin Lightening Practices Among Indonesian Adolescents - Nadia Khoirina; Wisnu Wardhana Putra; Abdullah Assagaf; Muhammad Yusuf; Sana Ullah (HM Publisher, 2025)
The proliferation of augmented reality (AR) filters on TikTok has introduced a hyper-idealized and often racialized standard of beauty. In Indonesia, where post-colonial ideals of whiteness persist, the algorithmic enforcement of light skin tones may exacerbate body dysmorphia. This study investigates the correlation between TikTok beauty filter usage and the intention to engage in skin bleaching practices, examining self-esteem as a mediating mechanism. A quantitative cross-sectional study was conducted using a stratified purposive sampling technique across five major provinces in Indonesia (n = 1,452 adolescent girls, aged 13–19). Participants completed an online survey measuring TikTok Filter Usage Intensity (TFUI), the Rosenberg Self-Esteem Scale (RSES), and the Skin Bleaching Intentions and Practices Scale (SBIPS). Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), incorporating Exploratory Factor Analysis (EFA) and Full Collinearity Assessment for Common Method Bias. High-intensity filter usage was significantly associated with lower self-esteem (beta = -0.42, p < 0.001) and higher skin bleaching intentions (beta = 0.38, p < 0.001). Self-esteem partially mediated the relationship between filter usage and bleaching practices (Variance Accounted For = 25.7%). The model demonstrated high predictive relevance (Q-square = 0.312) and explained 58.2% of the variance in skin bleaching intentions (R-square = 0.582). In conclusion, TikTok’s algorithmic filters serve as a significant predictor of chemical body modification behaviors. The digital whitening provided by filters creates a psychological gap, driving the consumption of skin-lightening products.